Ilmu Akuntansi dan Kepentingan Manusia - Titik Aryati (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2011)
AbstractThis paper aims to describe and explain the link between science and accounting with human interests. A famous philosopher, Jurgen Habermas (1990) states that science can not be separated from human interests. Accounting science is part of actions science that aimed to improving people's lives. Accounting theory used to predict and explain a phenomenon, that is related to human interests. Accounting and financial reporting environment is very complex because of the accounting product is information, an influential and important commodity. Accounting science has an interest for various parties such as, management, creditors, investors, governments, communities, and others. Besides accounting also has interests in various legal, environmental, ethics, public and others.Key words: science, accounting, and human interestsAbstractThis paper aims to describe and explain the link between science and accounting with human interests. A famous philosopher, Jurgen Habermas (1990) states that science can not be separated from human interests. Accounting science is part of actions science that aimed to improving people's lives. Accounting theory used to predict and explain a phenomenon, that is related to human interests.Accounting and financial reporting environment is very complex because of the accounting product isinformation, an influential and important commodity. Accounting science has an interest for variousparties such as, management, creditors, investors, governments, communities, and others. Besidesaccounting also has interests in various legal, environmental, ethics, public and others.Key words: science, accounting, and human interests